Value-added Product on Coffee Marketing in Pasuruan District - Lya Aklimawati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Development of household coffee industry can be used as a strategy to redistribute farmers’ household income. Through production process, farmer can create value-added by producing high value commercialized products. The objective of this research were to assess coffee price dynamics in Pasuruan district; and to analyze the value-added of coffee products produced by farmers. This research was carried out in Pasuruan district including Prigen, Tutur, Purwodadi, Purwosari, and Puspo sub-districts. Respondents were selected by using snowball  sampling method as much as 16 farmers. Data used in this research preferred primary data with secondary data as a supporting data. Data were analyzed with descriptive analysis, inductive analysis, and Hayami method. The results showed that the average of farmer’s share in Robusta coffee sales had exceeded 80% of the international market and Lampung spot market.  meanwhile, the average of farmer’s share in Arabica coffee sales was more than 40% of the international market and Medan spot market. Higher value-added could be created by conducting downstream processing as one of product diversification activities. Robustaand Arabica coffee which had been marketed as roasted coffee and ground coffee would provide a higher value-added than that of primary products (cherries, dried cherries, green bean). Based on these cases, farmers could gain the highest value-added by marketing ground coffee products.